Diversidade de cefalópodes e o seu papel no nicho trófico de seus principais predadores nos Arquipélagos de Fernando de Noronha e São Pedro e São Paulo - Andrade, Lorena Candice de Araújo (2008)
This study aims, to characterize the diversity of cephalopods by analyzing the stomach contents of fishes caught in the islands of St. Peter and St. Paul (ASPSP) and Fernando de Noronha (AFN). Also, verify the participation of cephalopods in the diet of their main predators. A total of 723 stomachs were collected, from 8 species of fish, caught by the fishery, 471 stomachs were from ASPSP and 252 were from the AFN. It was recorded the occurrence of food items (fish, cephalopods and crustaceans) and the cephalopods were identified to the lowest taxa possible, according to specialized literature. The Ommastrephidae family represented 84.46% of occurrence in the ASPSP and 63.48% in the AFN, confirming the importance of this family in the area studied and also in the diet of their predators. Among the species with greatest occurrence Ornitoteuthis antillarum was the most representative in both regions. This species had an average mantle length of 54.25 mm, thus demonstrating that the majority of this population is in the juvenile stage of development. The smallest species found was Argonauta nodosa with a mantle length of 4.06 mm and the largest was Ommastrephes bartrami, with 223.33 mm. In the AFN, the species richness (d) was 2.318, the diversity index (H ') was 1.454 and the measure of evenness (J) was 0.585. In the ASPSP, the species richness (d) was 2.66, the Shannon diversity index (H ') was 1.013 and the measure of evenness (J) was 0.373. AFN has a greater cephalopod diversity than ASPSP, confirming the pattern suggested by the Theory of Island Biogeography. Among the occurrence of prey items for all predators, the cephalopods are secondary preys. The most important cephalopod species in the diet of Thunnus albacares and Acantocybium solandri was Ornithoteuthis antillarum. These predators have different niche width the diet of Thunnus albacares is more specialized, but they have an overlap of 84.684% in the trophic niche, suggesting that in the ASPSP these two species may use similar niches